Implementation of Conceptual Change of Gas Kinetic Theory Material using Process Images - Indro Wicaksono; Linda Kurnia Supraptiningsih; Haritsah Alfad (Jurnal Pembelajaran Fisika, 2021)
The aim of this research is to implement the learning of conceptual changes in kinetic gas theory material using process drawings. This research is a pre-experimental with one-group pretest-posttest design for 30 students of XI IPA 7 MAN 2 Probolinggo City. The instrument used is a descriptive test of 6 questions. The results of the data analysis showed that the change in student concept after using process images in kinetic gas theory material increased with an average increase score of 0.51 (medium gain). This happens because students still experience misconceptions on the material laws of gas that are associated with the phenomena of daily life and the effective speed of gases theoretically.Keywords: conceptual change; gas kinetic theory; and process imagesDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202108